Finite-Element analysis of a lateral femoro-tibial impact on the total knee arthroplasty. (August 2020) - Arab, Ali Zine El-Abidine; Merdji, Ali; Benaissa, Ali; Roy, Sandipan; Bachir Bouiadjra, Bel-Abbes; Layadi, Khaled; Ouddane, Abdelhakim; Mukdadi, Osama M.
Highlights: 3D finite-element analysis provides an effective pre-operative method for planning patient-specific TKA prostheses. The stresses propagate in the bone regions adjacent to the TKA osseointegrated components. The important role of the polyethylene articulating spacer in absorbing impact combined forces generated during different daily activities. Implantation of a TKA system could be optimized using FEA in order to minimize the contact and interfacial stresses. Abstract: Background and Objective: Total knee arthroplasty (TKA) is a routine surgery performed to treat patients with severe knee osteoarthritis. The success of a TKA depends strongly on the initial stability of the prosthetic components and its long-term osseointegration due to the optimal distribution of mechanical stresses in the surrounding bones under the effect of the different biomechanical loads applied to the Femur-TKA-Tibia system. The purpose of this study is to analyze the level and the distribution of the induced stresses in a Femur-TKA-Tibia system subjected to combined triaxial forces, which mimic a femoral mechanical shock. Methods: In this study, complex TKA system implanted in both femoral and tibial bones has been analyzed numerically with a three-dimensional finite-element method. A virtual model is designed to examine in silico the effect of the combined triaxial forces acting on this prosthesis in femoral region. Anatomical three-dimensional finite-element models of both femoral and tibial bones were constructed to calculate the interfacial stresses around the TKA components. The 3D finite-element processing program ABAQUS was used to perform the analysis. Results: The stresses propagated in the bone regions adjacent to the TKA osseointegrated components, and the decreased in their magnitude to the outer region. These stresses reached the highest level in the cortical bone areas that are right next to the proximal upper attachment portions of the TKA osseointegrated components. The magnitude of the stresses in the tibial component is higher than that in the femoral component. Finally, it is very important to emphasize the role of the polyethylene articulating spacer in the shock absorption of bone support sections. Thus, this component should be preserved mechanically from the impact of high shocks in order to maintain healthy TKA systems. Conclusions: Optimizing TKA model by controlling the biomechanical stresses distributed within its both components and supporting bones is a valid approach to achieving favorable long-term outcomes. The 3D finite-element analysis provides an effective pre-operative method for planning patient-specific TKA prostheses, and for designing future models that preserves the biomechanical function of the Femur-TKA-Tibia system.